PEG-b-PLGA Nanoparticles Loaded with Geraniin from Phyllanthus Watsonii Extract as a Phytochemical Delivery Model - Kogilavanee Devasvaran; Sreegayathri Jairaman; Nur Azirah Yahaya; Indu Bala S. Jaganath; Yit Lung Khung; Vuanghao Lim; Siti Hawa Ngalim (Applied Sciences, 2020)
The study outlined a standardized double emulsion method for simple poly(ethylene glycol)-block-poly(lactic-co-glycolic acid) (PEG-b-PLGA) nanoparticle (NP) synthesis. The PEG-b-PLGA NP was also used for entrapment of geraniin as a simple model system for phytochemical delivery. PEG-b-PLGA NPs were prepared using the double emulsion method. The yields and particle sizes of PEG-b-PLGA NPs obtained with and without encapsulation of geraniin were 57.6% and 134.20 ± 1.45 nm and 66.7% and 102.70 ± 12.36 nm, respectively. High-performance liquid chromatography of geraniin that was extracted from Phyllanthus watsonii was detected at 64 min. Geraniin burst release began at 40 min and fully released at 3 h. PEG-b-PLGA NP was non-cytotoxic, while cytotoxicity of geraniin was dose dependant towards normal human epithelial colon cells, CCD 841 CoN cells.